PENGARUH KOMPETENSI, BUDAYA KERJA DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI PERWAKILAN BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL PROVINSI SULAWESI TENGAH - Sambali, Novayanti Prameta (Katalogis, 2015)
The puspose of t is to this research is to analyze yhe simultaneous and partial effects of competency, work culture, and office facilitation on officials‘ performance in BKKBN office of Central Sulawesi. The data is collected from questionnaires that were distributed to 78 respondents. The hypothesis is examined with multiple linear regressions. The research concludes that : 1) competency, work culture, and office facilitation simultaneously have positive and significant effects on official’s performance in BKKBN office of Central Sulawesi; 2) competency partially has positive and significant effects on officials’ performance in BKKBN office of Central Sulawesi; 3) work culture partially has positive and significant effects on official’s performance in BKKBN Office of Central Sulawesi; 4) office facilitation partially has positive and significant effects on officials’ performance in BKKBN office of Central Sulawesi. The result of determinant test shows Adjusted R-Square value of 0.650. This means that 65 % of employees’ performance in BKKBN office of Central Sulawesi is affected by competency, work culture, and facilitation at work. The remaining value of officials’ performance is affected by variables that are not studied.